Constipation and risk of death and cardiovascular events. (February 2019) - Sumida, Keiichi; Molnar, Miklos Z.; Potukuchi, Praveen K.; Thomas, Fridtjof; Lu, Jun Ling; Yamagata, Kunihiro; Kalantar-Zadeh, Kamyar; Kovesdy, Csaba P.
Abstract: Background and aims: Constipation is one of the most frequent symptoms encountered in daily clinical practice and is implicated in the development of atherosclerosis, potentially through altered gut microbiota. However, little is known about its association with incident cardiovascular events. Methods: In a nationally representative cohort of 3, 359, 653 US veterans with an estimated glomerular filtration rate (eGFR) ≥60 mL/min/1.73 m 2 between October 1, 2004 and September 30, 2006 (baseline period), with follow-up through 2013, we examined the association of constipation status (absence or presence; defined using diagnostic codes and laxative use) and laxative use (none, one, or ≥2 types of laxatives) with all-cause mortality, incident coronary heart disease (CHD), and incident ischemic stroke. Results: Among 3, 359, 653 patients, 237, 855 (7.1%) were identified as having constipation. After multivariable adjustments for demographics, prevalent comorbidities, medications, and socioeconomic status, patients with ( versus without) constipation had 12% higher all-cause mortality (hazard ratio [HR], 1.12; 95% CI, 1.11–1.13), 11% higher incidence of CHD (HR, 1.11; 95% CI, 1.08–1.14), and 19% higher incidence of ischemic stroke (HR, 1.19; 95% CI, 1.15–1.22). Patients with one and ≥2 ( versus none) types of laxatives experienced a similarly higher risk of all-cause mortality (HRs [95% CI], 1.15 [1.13–1.16] and 1.14 [1.12–1.15], respectively), incident CHD (HRs [95% CI], 1.11 [1.07–1.15] and 1.10 [1.05–1.15], respectively) and incident ischemic stroke (HRs [95% CI], 1.19 [1.14–1.23] and 1.21 [1.16–1.26], respectively). Conclusions: Constipation status and laxative use are independently associated with higher risk of all-cause mortality and incident CHD and ischemic stroke. Graphical abstract: Image 1 Highlights: Constipation and laxative use associate with higher risk of mortality. They also associate with higher incidence of coronary heart disease and stroke. Findings are robust to various sensitivity analyses.